A study of simulation modeling in door frame production - Wong, Eng How (2016)
This study discusses about assessing and enhancing the production line in door frame industries by using simulation method. The scope of this study is focusing on the production processes of a Door Frame Factory. The time frame covered is one year which is in year 2015. Simulation is a planning tool, implemented in the processes which required by the factory to meet the changing demands of the products. Modeling door frame production will be developed using Arena simulation software to test run and make comparison with the real world system. It is a quantitative study which the performance of the processes is measured by average wait time, machine utilization and operator utilization for the entire system of door frame production. The results obtained from the simulation software will act as an attempt to simulate the “What-If Analysis” scenarios to forecast the performance of real world system without developing costly implementation.